The effects of education on agricultural productivity under traditional and improved technology in northern Nigeria: an endogenous switching regression analysis - Alene, Arega D.; Manyong, Victor M. (Springer, 2007)
This paper estimates a more efficient version of an endogenous switching regression model to examine the effects of farmer education—schooling and extension contact—on cowpea production under traditional and improved technology in northern Nigeria. The results revealed significant productivity-enhancing effects of schooling and extension contact only under improved technology. Factors that promote technology adoption will thus indirectly raise the marginal contributions of farmer education; these include schooling, participatory technology evaluation, improved seed supply, and market access. The results demonstrate that schooling not only enhances agricultural productivity following technology adoption but also promotes adoption itself.